Isolated schwannoma of maxillary sinus: a rare occurrence - Francis, Glynis Florence; T. C., Vikram Raj Mohanam; M., Lakshanadeve V.; Kurien, Mary; Mohanraj, Anand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Schwannomas are benign tumors originating from the neural crests (schwann cells), which are cells that form the nerve sheath of peripheral nerve fibers. Around 25-45% cases of schwannomas occur in the head and neck, of which less than 4% occurs in the nasal cavity and the paranasal sinuses. Isolated schwannomas of the maxillary sinus appear to be extremely rare. We report a case of an isolated maxillary schwannoma in a 45 years old lady who presented with swelling in the right cheek for 1 year and right sided nasal obstruction for 4 months. The swelling was not associated with epistaxis, fever, headache or visual disturbances. We report this case keeping in mind the rarity in occurrence of isolated maxillary schwannomas